Honeycomb structure, and electrically heated carrier and exhaust gas treatment device using said honeycomb structure

The honeycomb structure with a porous electrode portion made of silicon carbide and a binder addresses the challenge of uniform energization in EHCs, achieving adjustable resistance and effective heat distribution for efficient exhaust gas treatment.

JP7663387B2Active Publication Date: 2025-04-16NGK CORP
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2021050434
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-24
Publication Date
2025-04-16
Estimated Expiration
2041-03-24

AI Technical Summary

Technical Problem

Existing honeycomb structures used in electric heating catalysts (EHCs) face challenges in uniformly energizing the honeycomb structure portion, particularly in adjusting resistance in a low resistance region.

Method used

A honeycomb structure with an electrode portion made of a porous body where silicon carbide particles are bonded by a binder, including α-type and β-type silicon carbide, with a D50 particle size of 25 μm or less, and a volume resistivity range of 0.01 Ω·cm to 2.0 Ω·cm.

Benefits of technology

The honeycomb structure allows for adjustable resistance in a low resistance region, enabling uniform heating and effective heat distribution, which is essential for efficient exhaust gas treatment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007663387000002
    Figure 0007663387000002
  • Figure 0007663387000003
    Figure 0007663387000003
  • Figure 0007663387000001
    Figure 0007663387000001
Patent Text Reader

Abstract

To provide a honeycomb structure including electrode portions each capable of having its resistance adjusted in a low-resistance region.SOLUTION: A honeycomb structure includes: a honeycomb structure portion having: an outer peripheral wall; and a partition wall arranged inside the outer peripheral wall to define a plurality of cells each extending from a first end surface of the honeycomb structure portion to a second end surface thereof to form a flow path; and a pair of electrode portions arranged on an outer peripheral surface of the outer peripheral wall of the honeycomb structure portion. The electrode portions are composed of a porous body in which particles of silicon carbide are bound by a binding material. The silicon carbide contains α-type silicon carbide and β-type silicon carbide. The silicon carbide has a D50 in a volume-based cumulative particle size distribution of 25 μm or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a honeycomb structure, and an electrically heated carrier and an exhaust gas treatment device using the honeycomb structure. [Background technology]

[0002] In recent years, electrically heated catalysts (EHCs) have been proposed to improve the deterioration of exhaust gas purification performance immediately after engine start. EHCs are constructed by arranging electrodes in a honeycomb structure made of conductive ceramic, and heating the honeycomb structure itself by passing electricity through it, thereby raising the temperature of the catalyst supported on the honeycomb structure to an activation temperature before or when the engine is started.

[0003] As a honeycomb structure used in EHC, for example, a honeycomb structure having a honeycomb structure part and an electrode part (paste electrode) provided on the honeycomb structure part is known. In the technical field of EHC, various studies have been made on the resistance adjustment of the paste electrode in order to uniformly pass electricity through the honeycomb structure part having a predetermined volume resistivity. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Patent No. 5883795 [Patent Document 2] International Publication No. 2020 / 246004 [Patent Document 3] Patent No. 6364374 [Patent Document 4] Patent No. 6778644 [Patent Document 5] Patent No. 5965862 Summary of the Invention [Problem to be solved by the invention]

[0005] A primary object of the present invention is to provide a honeycomb structure having an electrode portion capable of adjusting the resistance in a low resistance region. A further object of the present invention is to provide an electrically heated carrier and an exhaust gas treatment device using such a honeycomb structure. [Means for solving the problem]

[0006] A honeycomb structure according to an embodiment of the present invention includes a honeycomb structure portion having an outer peripheral wall and partition walls disposed inside the outer peripheral wall and defining a plurality of cells extending from a first end face to a second end face to form a flow path; and a pair of electrode portions disposed on an outer peripheral surface of the outer peripheral wall of the honeycomb structure portion. The electrode portions are formed of a porous body in which silicon carbide particles are bound by a binder. The silicon carbide includes α-type silicon carbide and β-type silicon carbide. The silicon carbide has a D50 of 25 μm or less in a cumulative particle size distribution based on volume. In one embodiment, the α-type silicon carbide has a D50 of 10 μm to 45 μm, and the β-type silicon carbide has a D50 of 10 μm to 45 μm. In one embodiment, the content of the α-type silicon carbide in the silicon carbide is 5% by mass to 95% by mass. In one embodiment, the electrode portion has a volume resistivity of 0.01 Ω·cm to 2.0 Ω·cm. In one embodiment, the bond material comprises silicon metal and / or a metal silicide. According to another aspect of the present invention, there is provided an electrically heated carrier, the electrically heated carrier having the above-mentioned honeycomb structure and a pair of metal terminals provided on the pair of electrode portions of the honeycomb structure. In one embodiment, the electrically heated support further includes a base layer provided between the electrode portion of the honeycomb structure and the metal terminal. According to yet another aspect of the present invention, there is provided an exhaust gas treatment device, comprising: the electrically heated carrier described above; and a can body that holds the electrically heated carrier. Effect of the Invention

[0007] According to the embodiment of the present invention, it is possible to realize a honeycomb structure having electrode parts whose resistance can be adjusted in a low resistance region. [Brief description of the drawings]

[0008] [Figure 1] 1 is a schematic perspective view of a honeycomb structure according to one embodiment of the present invention. [Diagram 2] 2 is a schematic cross-sectional view of the honeycomb structure of FIG. 1 in a direction parallel to the flow path direction of exhaust gas. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] Hereinafter, embodiments of the present invention will be described with reference to the drawings, but the present invention is not limited to these embodiments.

[0010] A. Honeycomb structure A-1. Overall configuration of honeycomb structure FIG. 1 is a schematic perspective view of a honeycomb structure according to one embodiment of the present invention, and FIG. 2 is a schematic cross-sectional view of the honeycomb structure of FIG. 1 in a direction parallel to the flow path direction of exhaust gas. The honeycomb structure 200 of the illustrated example includes a honeycomb structure part 100 and a pair of electrode parts 120, 120 arranged on the side surface of the honeycomb structure part 100. The honeycomb structure part 100 has an outer peripheral wall 40 and partition walls 30 arranged inside the outer peripheral wall 40 and defining a plurality of cells 20 that extend from a first end face 10a to a second end face 10b and form a flow path. In FIG. 2, the fluid can flow in either the left or right direction of the paper. The fluid may be any suitable liquid or gas depending on the purpose. For example, when the honeycomb structure is used in an electrically heated carrier described later, the fluid is preferably exhaust gas.

[0011] The electrode parts are disposed, for example, on the outer peripheral surface of the outer peripheral wall of the honeycomb structure part. In the illustrated example, the electrode parts 120, 120 are disposed on the outer peripheral surface of the outer peripheral wall 40 across the central axis of the honeycomb structure part 100 (typically, at positions symmetrical with respect to the central axis). The electrode parts 120, 120 are typically disposed in a strip shape extending along the flow direction of the honeycomb structure part, and are disposed over the entire flow direction of the honeycomb structure part (i.e., from the first end face 10a to the second end face 10b) as in the illustrated example. With this configuration, the honeycomb structure part can generate heat uniformly. The width of each of the electrode parts 120, 120 is such that the central angle (the angle defined by the central axis and the line connecting both ends of each electrode part) in the cross section in the direction perpendicular to the flow direction of the honeycomb structure part is, for example, 15° to 65°, or, for example, 30° to 60°. With this configuration, due to a synergistic effect with the effect of setting the length in the flow passage direction as described above, it is possible to make the honeycomb structure section generate heat more uniformly.

[0012] In the embodiment of the present invention, the electrode parts 120, 120 are made of a porous body in which silicon carbide particles are bound by a binder. Furthermore, the silicon carbide includes α-type silicon carbide and β-type silicon carbide, and D50 in the cumulative particle size distribution based on volume of the silicon carbide is 25 μm or less.

[0013] A-2. Honeycomb structure The shape of the honeycomb structure part can be appropriately designed depending on the purpose. The honeycomb structure part 100 in the illustrated example is cylindrical (the cross-sectional shape in the direction perpendicular to the cell extension direction is circular), but the honeycomb structure part may be a columnar shape having an elliptical or polygonal cross-sectional shape (for example, a quadrilateral, pentagon, hexagon, heptagon, or octagon). The length of the honeycomb structure part can be appropriately set depending on the purpose. The length of the honeycomb structure part can be, for example, 5 mm to 250 mm, or 10 mm to 150 mm, or 20 mm to 100 mm. The diameter of the honeycomb structure part can be appropriately set depending on the purpose. The diameter of the honeycomb structure part can be, for example, 20 mm to 200 mm, or 30 mm to 100 mm. In addition, when the cross-sectional shape of the honeycomb structure part is not circular, the diameter of the honeycomb structure part can be the diameter of the maximum inscribed circle inscribed in the cross-sectional shape (for example, polygon) of the honeycomb structure part.

[0014] The partition walls 30 and the outer peripheral wall 40 are typically made of ceramics containing silicon carbide and silicon (hereinafter, sometimes referred to as silicon carbide-silicon composite material). The ceramics contain silicon carbide and silicon in a total amount of, for example, 90 mass % or more, for example, 95 mass % or more. With such a configuration, the volume resistivity of the honeycomb structure part at 25°C can be set within a predetermined range. The volume resistivity of the honeycomb structure part is preferably 0.1 Ω·cm to 200 Ω·cm, and more preferably 1.0 Ω·cm to 200 Ω·cm. According to an embodiment of the present invention, by making the electrode part into a predetermined configuration as described later, it is possible to uniformly pass electricity through a honeycomb structure part having such a volume resistivity. The ceramics may contain a substance other than the silicon carbide-silicon composite material. An example of such a substance is strontium.

[0015] The silicon carbide-silicon composite typically contains silicon carbide particles as aggregates and silicon as a binder for binding the silicon carbide particles. In the silicon carbide-silicon composite, for example, a plurality of silicon carbide particles are bound by silicon so as to form pores between the silicon carbide particles. That is, the partition wall 30 and the outer peripheral wall 40 containing the silicon carbide-silicon composite may be, for example, a porous body.

[0016] The silicon content in the silicon carbide-silicon composite material is preferably 10% by mass to 40% by mass, and more preferably 15% by mass to 35% by mass. If the silicon content is too low, the strength of the honeycomb structure (and, as a result, the honeycomb structure) may be insufficient. If the silicon content is too high, the honeycomb structure may not be able to maintain its shape when fired.

[0017] The average particle diameter of the silicon carbide particles is preferably 3 μm to 50 μm, more preferably 3 μm to 40 μm, and further preferably 10 μm to 35 μm. When the average particle diameter of the silicon carbide particles is in this range, the volume resistivity of the honeycomb structure portion can be set to the appropriate range as described above. If the average particle diameter of the silicon carbide particles is too large, the raw material may clog the die when forming a honeycomb formed body, which is the precursor of the honeycomb structure portion. The average particle diameter of the silicon carbide particles can be measured, for example, by a laser diffraction method.

[0018] The average pore diameter of the partition walls 30 and the outer peripheral wall 40 is preferably 2 μm to 20 μm, more preferably 2 μm to 15 μm, and further preferably 4 μm to 8 μm. When the average pore diameter of the partition walls is in this range, the volume resistivity can be set to the above-mentioned appropriate range. The average pore diameter can be measured, for example, by a mercury porosimeter.

[0019] The porosity of the partition walls 30 and the peripheral wall 40 is preferably 15% to 60%, and more preferably 30% to 45%. If the porosity is too small, the honeycomb structure may be significantly deformed during firing. If the porosity is too large, the strength of the honeycomb structure may be insufficient. The porosity can be measured, for example, by a mercury porosimeter.

[0020] The thickness of the partition walls 30 can be appropriately set depending on the purpose. The thickness of the partition walls 30 is, for example, 50 μm to 0.3 mm, and can be, for example, 150 μm to 250 μm. When the thickness of the partition walls is within this range, the mechanical strength of the honeycomb structure portion (and thus the honeycomb structure) can be made sufficient, and the opening area (total area of ​​cells in the cross section) can be made sufficient, and when the honeycomb structure is used as a catalyst carrier, pressure loss during the flow of exhaust gas can be suppressed.

[0021] The density of the partition walls 30 can be appropriately set depending on the purpose. The density of the partition walls 30 is, for example, 0.5 g / cm 3 ~5.0g / cm 3 If the density of the partition walls is within this range, the weight of the honeycomb structure part (and thus the honeycomb structure) can be reduced, and the mechanical strength can be made sufficient. The density can be measured, for example, by the Archimedes method.

[0022] In one embodiment, the thickness of the outer peripheral wall 40 is greater than the thickness of the partition wall 30. With this configuration, it is possible to suppress the destruction, breakage, cracking, etc. of the outer peripheral wall due to external forces (for example, impact from the outside, thermal stress due to the temperature difference between the exhaust gas and the outside). The thickness of the outer peripheral wall 40 is, for example, 0.05 mm or more, preferably 0.1 mm or more, and more preferably 0.15 mm or more. However, if the outer peripheral wall is made too thick, the heat capacity increases, the temperature difference between the inner peripheral side of the outer peripheral wall and the partition wall on the inner peripheral side increases, and the thermal shock resistance decreases, so the thickness of the outer peripheral wall is preferably 1.0 mm or less, more preferably 0.7 mm or less, and even more preferably 0.5 mm or less.

[0023] The cells 20 have any appropriate cross-sectional shape in a direction perpendicular to the cell extension direction. In the illustrated example, the partition walls 30 that define the cells are perpendicular to each other, and define the cells 20 having a quadrangular (square in the illustrated example) cross-sectional shape except for the portion in contact with the outer peripheral wall 40. The cross-sectional shape of the cells 20 may be a square, a triangle, a pentagon, a hexagon or more polygonal shape, etc. The cross-sectional shape of the cells is preferably a rectangle or a hexagon. Such a configuration has the advantage that the pressure loss when exhaust gas flows is small and the purification performance is excellent.

[0024] The cell density in the direction perpendicular to the extension direction of the cells 20 (i.e., the number of cells 20 per unit area) can be appropriately set depending on the purpose. The cell density is preferably 40 cells / cm. 2 ~150 cells / cm 2 and more preferably 50 cells / cm 2 ~150 cells / cm 2 and more preferably 70 cells / cm 2 ~100 cells / cm 2 If the cell density is within this range, the strength of the honeycomb structure and the effective GSA (geometric surface area, i.e., catalyst carrying area) are sufficiently ensured, and the pressure loss when exhaust gas flows through it can be suppressed.

[0025] A-3. Electrode part As described above, the electrode part is composed of a porous body in which silicon carbide particles are bound by a binder. Representative examples of the binder include metal silicon and metal silicide. These may be used alone or in combination. Metals constituting the metal silicide include, for example, nickel, zirconium, and combinations thereof. In the electrode part, for example, a plurality of silicon carbide particles are bound by a binder so as to form pores between the silicon carbide particles. The content of silicon carbide in the electrode part is preferably 50% by mass to 90% by mass, more preferably 60% by mass to 80% by mass, and further preferably 65% ​​by mass to 75% by mass. The content of the binder in the electrode part is preferably 10% by mass to 50% by mass, and more preferably 20% by mass to 40% by mass. If the contents of silicon carbide and binder are within such ranges, sufficient SiC bond strength can be obtained. If there is an excess of the binder (typically silicon metal), there is a possibility that the binder (typically silicon metal) may not be maintained within the structure during manufacturing.

[0026] In the embodiment of the present invention, silicon carbide includes α-type silicon carbide (hereinafter, sometimes referred to as α-SiC) and β-type silicon carbide (hereinafter, sometimes referred to as β-SiC). By using a combination of α-SiC and β-SiC in the electrode part, it is possible to form an electrode part capable of adjusting the resistance in a low resistance region. With α-SiC alone, a low resistance electrode part may not be realized. With β-SiC alone, the resistance becomes too low, and there is a risk of excessive current flowing locally in the electrode part. The content of α-SiC in silicon carbide is preferably 5% by mass to 95% by mass. The content of α-SiC may be, for example, 5% by mass to 30% by mass, or 5% by mass to 15% by mass, or 10% by mass to 50% by mass, or 10% by mass to 30% by mass, or 20% by mass to 80% by mass, or 30% by mass to 70% by mass, or 30% by mass to 50% by mass, or 50% by mass to 70% by mass, or 70% by mass to 95% by mass, or 85% by mass to 95% by mass. If the content of α-SiC in silicon carbide is within such a range, the above-mentioned effect becomes more remarkable. In this specification, the term "SiC" is intended to include not only pure SiC but also SiC containing unavoidable impurities.

[0027] In the embodiment of the present invention, the D50 in the cumulative particle size distribution based on volume of silicon carbide is 25 μm or less, preferably 5 μm to 25 μm, more preferably 10 μm to 25 μm, and further preferably 10 μm to 20 μm, as described above. If the D50 of silicon carbide is in such a range, when a base layer (for example, a sprayed base layer) is formed between the electrode part and the metal terminal in the electrically heated support described later, good continuity with the base layer can be ensured. The D50 of silicon carbide may be, for example, 20 μm or less, or, for example, 18 μm or less, or, for example, 15 μm or less.

[0028] D10 in the cumulative particle size distribution on a volume basis of silicon carbide is preferably 3 μm to 20 μm, and more preferably 5 μm to 15 μm.D90 in the cumulative particle size distribution on a volume basis of silicon carbide is preferably 15 μm to 65 μm, and more preferably 15 μm to 55 μm.

[0029] The D50 of α-SiC is preferably 10 μm to 45 μm. The D50 of α-SiC may be, for example, 10 μm to 18 μm, or may be, for example, 10 μm to 15 μm, or may be, for example, 25 μm to 45 μm, or may be, for example, 30 μm to 45 μm. If the D50 of α-SiC is in such a range, it is possible to form an electrode part that can adjust the resistance in a more appropriate low resistance region and maintain the adjusted resistance value more stably. Furthermore, when a base layer (for example, a sprayed base layer) is formed between the electrode part and the metal terminal in the electrically heated support described later, good continuity with the base layer can be ensured. The D50 of β-SiC is preferably 10 μm to 45 μm, and more preferably 18 μm to 25 μm.

[0030] D10 of α-SiC is preferably 3 μm to 30 μm, more preferably 5 μm to 20 μm. D90 of α-SiC is preferably 10 μm to 90 μm, more preferably 15 μm to 80 μm, and further preferably 15 μm to 60 μm. D10 of β-SiC is preferably 3 μm to 30 μm, more preferably 5 μm to 20 μm. D90 of α-SiC is preferably 10 μm to 90 μm, more preferably 15 μm to 65 μm, and more preferably 20 μm to 65 μm. D10, D50, and D90 of α-SiC and D10, D50, and D90 of β-SiC can be measured by, for example, a laser diffraction method.

[0031] The volume resistivity of the electrode portion is preferably 0.01 Ω·cm to 2.0 Ω·cm, more preferably 0.05 Ω·cm to 1.8 Ω·cm, further preferably 0.07 Ω·cm to 1.6 Ω·cm, and particularly preferably 0.07 Ω·cm to 1.2 Ω·cm. By using a combination of α-SiC and β-SiC in the electrode portion, it is possible to adjust the resistance in such a low resistance region, and the adjusted resistance value can be stably maintained. In particular, according to the embodiment of the present invention, even if the volume resistivity of the honeycomb structure portion fluctuates, good heat generation distribution can be realized during electrical heating by controlling the volume resistivity of the electrode portion to a range of 0.07 Ω·cm to 1.2 Ω·cm. The volume resistivity of the electrode portion is a value measured at 25°C by a four-terminal method.

[0032] The porosity of the electrode part is preferably 15% to 60%, more preferably 18% to 50%, and further preferably 19% to 40%. The porosity can be determined, for example, from an image of the cross section of the electrode part observed with a scanning electron microscope (SEM) using image processing software.

[0033] The thickness of the electrode part is preferably 50 μm to 300 μm, more preferably 100 μm to 200 μm, and further preferably 100 μm to 150 μm. When the thickness of the electrode part is within this range, the honeycomb structure part can be uniformly heated, and the electrode part having good thermal shock resistance can be formed. If the thickness of the electrode part is too thin, it may be difficult to uniformly heat the honeycomb structure part. If the thickness of the electrode part is too thick, the thermal shock resistance of the electrode part may be insufficient.

[0034] A-4. Manufacturing method of honeycomb structure The honeycomb structure may be manufactured by any suitable method, and a representative example will be described below.

[0035] First, a honeycomb structure forming raw material (hereinafter, sometimes simply referred to as forming raw material) is prepared by adding metal silicon powder, binder, surfactant, pore former, water, etc. to silicon carbide powder. As described in the above item A-2, the metal silicon powder can be mixed in an amount of preferably 10 mass% to 40 mass% with respect to the total mass of the silicon carbide powder and the metal silicon powder. As described in the above item A-2, the average particle diameter of the silicon carbide particles in the silicon carbide powder is preferably 3 μm to 50 μm. The average particle diameter of the metal silicon particles in the metal silicon powder is preferably 2 μm to 35 μm. If the average particle diameter of the metal silicon particles is too small, the volume resistivity of the obtained honeycomb structure may be excessively small. If the average particle diameter of the metal silicon particles is too large, the volume resistivity of the obtained honeycomb structure may be excessively large. The total content of silicon carbide powder and metal silicon powder can be appropriately set according to the desired structure of the honeycomb structure to be obtained. The total content is preferably 30 mass% to 78 mass% based on the total mass of the forming raw material. The average particle size of the metal silicon particles can be measured, for example, by laser diffraction method.

[0036] Examples of the binder include methyl cellulose, hydroxypropoxyl cellulose, hydroxyethyl cellulose, carboxymethyl cellulose, and polyvinyl alcohol. Among these, it is preferable to use methyl cellulose and hydroxypropoxyl cellulose in combination. The content of the binder can also be appropriately set according to the desired configuration of the honeycomb structure to be obtained. The content of the binder is preferably 2% by mass to 10% by mass relative to 100 parts by mass of the total mass of the silicon carbide powder and the metallic silicon powder.

[0037] Examples of the surfactant include ethylene glycol, dextrin, fatty acid soap, and polyalcohol. These may be used alone or in combination of two or more. The content of the surfactant may also be appropriately set according to the desired configuration of the honeycomb structure to be obtained. The content of the surfactant is preferably 0.1% by mass or more and 2% by mass or less relative to 100 parts by mass of the total mass of the silicon carbide powder and the metallic silicon powder.

[0038] Any suitable material can be used as the pore-forming material as long as it disappears by firing to form pores. Examples of the pore-forming material include graphite, starch, foamed resin, water-absorbent resin, and silica gel. The content of the pore-forming material can also be appropriately set according to the desired configuration of the honeycomb structure to be obtained. The content of the pore-forming material is preferably 0.5% by mass or more and 10% by mass or less with respect to 100 parts by mass of the total mass of the silicon carbide powder and the metal silicon powder. The average particle diameter of the pore-forming material is preferably 10 μm to 30 μm. If the average particle diameter of the pore-forming material is too small, pores may not be sufficiently formed. If the average particle diameter of the pore-forming material is too large, the forming raw material may clog the die during forming. The average particle diameter of the pore-forming material can be measured, for example, by a laser diffraction method.

[0039] The water content can also be appropriately set depending on the desired structure of the honeycomb structure to be obtained. The water content is preferably 20 mass % to 60 mass % relative to 100 parts by mass of the total mass of the silicon carbide powder and the silicon metal powder.

[0040] Next, the forming raw materials are kneaded to form a puddle. Any appropriate device or mechanism can be used as the kneading means. Specific examples include a kneader and a vacuum kneader.

[0041] Next, the clay is extruded to form a honeycomb molded body. In extrusion molding, a die having a configuration corresponding to the desired overall shape, cell shape, partition wall thickness, cell density, etc. of the honeycomb structure part can be used. The die material can be, for example, a hard alloy that is resistant to wear. The partition wall thickness, cell density, outer peripheral wall thickness, etc. of the honeycomb molded body (i.e., the configuration of the die) can be appropriately set corresponding to the desired configuration of the obtained honeycomb structure part, taking into account the shrinkage during drying and firing described below.

[0042] Next, the honeycomb molded body is dried to obtain a dried honeycomb body. Any appropriate method can be used as the drying method. Specific examples include electromagnetic heating methods such as microwave heating drying and dielectric heating drying (for example, high-frequency dielectric heating drying); and external heating methods such as hot air drying and superheated steam drying. In one embodiment, two-stage drying can be performed. The two-stage drying includes drying a certain amount of moisture by the electromagnetic heating method, and then drying the remaining moisture by the external heating method. According to such two-stage drying, the entire molded body can be dried quickly and uniformly without causing cracks. More specifically, the two-stage drying includes removing 30 mass% to 99 mass% of moisture with respect to the moisture content of the honeycomb molded body before drying by the electromagnetic heating method, and then reducing the moisture content of the dried honeycomb body to 3 mass% or less by the external heating method. As the electromagnetic heating method, dielectric heating drying is preferable, and as the external heating method, hot air drying is preferable.

[0043] Next, the dried honeycomb body is fired to obtain a honeycomb structure part. In one embodiment, pre-firing may be performed before firing. By performing pre-firing, the binder and the like can be removed well. Pre-firing may be performed, for example, in an air atmosphere at 400°C to 500°C for 0.5 to 20 hours. Firing may be performed, for example, in an inert atmosphere such as nitrogen or argon, at 1400°C to 1500°C for 1 to 20 hours. Pre-firing and firing may be performed using any appropriate means. Pre-firing and firing may be performed, for example, using an electric furnace or a gas furnace.

[0044] Finally, a pair of electrode parts are formed at predetermined positions of the honeycomb structure part (for example, on the outer peripheral surface of the outer wall sandwiching the central axis of the honeycomb structure part as shown in Fig. 1) to obtain a honeycomb structure. The electrode parts are formed by applying an electrode part forming paste to predetermined positions of the honeycomb structure part, and drying and firing the applied electrode part forming paste.

[0045] The electrode part forming paste contains silicon carbide powder, metal silicon powder and / or metal silicide powder, and, as necessary, a binder, a surfactant, a pore former, water, etc. The silicon carbide powder contains α-SiC and β-SiC in a predetermined ratio as described in the above item A-3. Furthermore, as described in the above item A-3, the D50 of silicon carbide is 25 μm or less, the D50 of α-SiC is preferably 10 μm to 45 μm, and the D50 of β-SiC is preferably 10 μm to 45 μm. The compounding ratio of the silicon carbide powder to the metal silicon powder and / or metal silicide powder can be adjusted according to the content of silicon carbide and the binder as described in the above item A-3.

[0046] The binder, surfactant, pore former, water, etc. are as described above with respect to the honeycomb structure forming raw material. Drying and firing are also as described above with respect to the formation of the honeycomb structure.

[0047] The above describes an embodiment in which an electrode portion is formed on a honeycomb structure portion (i.e., after firing of the dried honeycomb body), but it is also possible to apply an electrode portion forming paste to the dried honeycomb body (before firing) and then fire it to form the honeycomb structure portion and the electrode portion simultaneously.

[0048] In this manner, a honeycomb structure can be manufactured.

[0049] B. Electrically heated carrier The honeycomb structure according to the embodiment of the present invention can be suitably used as an electrically heated carrier. Therefore, an electrically heated carrier using such a honeycomb structure can also be included in the embodiment of the present invention. The electrically heated carrier according to the embodiment of the present invention includes the honeycomb structure 200 described in the above item A and metal terminals (not shown) provided on the electrode parts 120, 120 of the honeycomb structure 200. One metal terminal is connected to the positive pole of a power source (e.g., a battery), and the other metal terminal is connected to the negative pole of the power source (e.g., a battery). If necessary, a base layer may be formed between the electrode part and the metal terminal. The base layer serves as a base for laser welding or thermal spraying when joining with the metal terminal, and preferably has a function as a stress relaxation layer. That is, when the difference in linear expansion coefficient between the electrode part and the metal terminal is large, there is a possibility that the electrode part will crack due to thermal stress. Therefore, it is preferable that the base layer has a function of relaxing thermal stress caused by the difference in linear expansion coefficient between the electrode part and the metal terminal. This makes it possible to suppress the occurrence of cracks in the electrode portion due to fatigue caused by repeated thermal cycles and / or when the metal terminal is joined to the electrode portion. The underlayer may be formed by thermal spraying or by firing a paste for forming the underlayer.

[0050] The metal terminals may be a pair of metal terminals arranged such that one metal terminal faces the other metal terminal across the central axis of the honeycomb structure. When a voltage is applied to the metal terminals via the electrode parts, the metal terminals are energized and can generate heat in the honeycomb structure by Joule heat. For this reason, the electrically heated carrier can also be suitably used as a heater. The voltage to be applied can be appropriately set depending on the purpose. The voltage to be applied may be, for example, 12 V to 900 V, or may be, for example, 48 to 600 V.

[0051] The material of the metal terminal may be any suitable metal. For example, a single metal or an alloy may be used. From the viewpoints of corrosion resistance, electrical resistivity, and linear expansion coefficient, for example, an alloy containing at least one selected from Cr, Fe, Co, Ni, and Ti is preferable, and stainless steel and an Fe-Ni alloy are more preferable.

[0052] The material of the underlayer is not particularly limited. For example, a composite material (cermet) of metal and ceramics (particularly conductive ceramics) can be used as the material of the underlayer. However, it is preferable that the material be one that can reduce the thermal expansion difference between the electrode portion and the metal terminal.

[0053] The configuration of the underlayer is not particularly limited. The underlayer preferably contains one or more metals selected from, for example, Ni-based alloys, Fe-based alloys, Ti-based alloys, Co-based alloys, metal silicon, and Cr. More preferably, the underlayer is composed of Ni-based alloys, Fe-based alloys, Ti-based alloys, or Co-based alloys. Examples of Ni-based alloys include Inconel and Hastelloy. Examples of Fe-based alloys include stainless steels such as SUS430. Examples of Ti-based alloys include JIS 60 (ASTM B348 Gr5). Examples of Co-based alloys include Stellite. This is due to the heat resistance at 600 to 800°C. Among these, Fe-based alloys (e.g., ferritic stainless steel) are preferred because the thermal expansion difference with the honeycomb structure is small and thermal stress can be reduced.

[0054] In one embodiment, the underlayer may contain one or more ceramics selected from oxide ceramics such as alumina, mullite, zirconia, glass, and cordierite, and non-oxide ceramics such as silicon carbide, silicon nitride, and aluminum nitride, for the reasons of adjusting the thermal expansion coefficient so as to relieve stress caused by the difference in thermal expansion between the metal terminal and the electrode portion, and for the reasons of suppressing oxidation of the metal contained in the underlayer.

[0055] In one embodiment, the undercoat layer is made of a composite material containing stainless steel and glass. Examples of glass include borosilicate glass, aluminosilicate glass, and soda-lime glass. Examples of aluminosilicate glass include Mg-Al-Si oxides (e.g., MgO-Al 2 O 3 -SiO 2 ) are mentioned.

[0056] In the electrically heated carrier, typically, a catalyst can be supported on the partition walls 30 of the honeycomb structure 200. By supporting a catalyst on the partition walls, when exhaust gas is caused to flow through the cells 20, CO, NO x , hydrocarbons, etc. can be converted into harmless substances by catalytic reaction. The catalyst may preferably contain noble metals (e.g., platinum, rhodium, palladium, ruthenium, indium, silver, gold), aluminum, nickel, zirconium, titanium, cerium, cobalt, manganese, zinc, copper, tin, iron, niobium, magnesium, lanthanum, samarium, bismuth, barium, and combinations thereof. These elements may be contained as simple metals, metal oxides, or other metal compounds. The amount of the catalyst supported may be, for example, 0.1 g / L to 400 g / L.

[0057] When a voltage is applied to the honeycomb structure 200 in the electrically heated carrier, electricity is passed therethrough, and the honeycomb structure can be heated by Joule heat. This allows the catalyst supported on the honeycomb structure (substantially the partition walls) to be heated to an active temperature before or at the time of engine start. As a result, exhaust gas can be sufficiently treated (representatively purified) even at the time of engine start.

[0058] C. Exhaust gas treatment equipment The electrically heated carrier according to the embodiment of the present invention can be suitably used in an exhaust gas treatment device. Therefore, an exhaust gas treatment device using such an electrically heated carrier can also be included in the embodiment of the present invention. The exhaust gas treatment device according to the embodiment of the present invention includes the electrically heated carrier described in the above section B and a can body that holds the electrically heated carrier. The can body is any appropriate cylindrical member (e.g., made of metal). The exhaust gas treatment device is typically installed in the middle of an exhaust gas flow path for flowing exhaust gas from an automobile engine. EXAMPLES

[0059] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. The evaluation items in the examples are as follows. In addition, "parts" and "%" in the examples are based on mass unless otherwise specified.

[0060] (1) Volume resistivity The volume resistivity of the electrode portion was measured at 25°C by the four-terminal method. Specifically, a measurement sample for measuring the volume resistivity was prepared by cutting out the electrode portion of the honeycomb structure. Silver paste was applied to the entire surface of both ends of the prepared measurement sample, and wiring was performed to enable electrical current to flow. A voltage application current measurement device was connected to the measurement sample and applied. A voltage of 10 V to 200 V was applied, and the current and voltage values ​​at 25°C were measured, and the volume resistivity (Ω·cm) was calculated from the obtained current and voltage values ​​and the dimensions of the test piece. If the volume resistivity value is within the range of 0.07 Ω·cm to 1.2 Ω·cm, the resistance of the electrode portion is suitably adjusted to a low resistance region.

[0061] (2) Porosity The porosity of the electrode portion was measured by a mercury porosimeter.

[0062] (3) Particle size The grain size of silicon carbide was measured by the following method. An electrode portion was cut out from a honeycomb structure, and components other than silicon carbide were dissolved by acid treatment. Then, only silicon carbide was taken out, washed and dried, and the grain size was measured by a laser diffraction method.

[0063] (4) Continuity with the thermal sprayed base layer The continuity with the thermal sprayed base layer was evaluated as follows. The heat distribution between the thermal sprayed base layer and the electrode part was confirmed when 1.0 kW to 2.0 kW of power was applied to the electrode part. The heat distribution was confirmed by thermography and visually judged according to the following evaluation criteria. ◎ (Excellent): No localized heat generation at the boundary between the electrode layer and the thermal spray base layer ○ (Good): Slight localized heat generation at the boundary between the electrode layer and the thermal spray base layer × (bad): Significant localized heat generation at the boundary between the electrode layer and the thermal spray base layer

[0064] <Example 1> After the clay containing the metal silicon powder and the silicon carbide powder was extruded, it was dried to obtain a honeycomb dried body having a shape as shown in FIG. 1. Next, a pair of electrodes were formed at positions facing each other across the central axis of the obtained honeycomb dried body. Specifically, it was as follows. 30 parts of metal silicon powder, 35 parts of α-type silicon carbide powder, 35 parts of β-type silicon carbide powder, 0.5 parts of methylcellulose, 10 parts of glycerin, and 38 parts of water were mixed with a rotating and revolving mixer to prepare an electrode forming paste. The obtained electrode forming paste was applied to the above-mentioned electrode forming position. The honeycomb dried body to which the electrode forming paste was applied was degreased and fired to obtain a honeycomb structure. The degreasing was performed in the atmosphere at 450°C for 5 hours. The firing was performed in an argon atmosphere at 1450°C for 2 hours. Here, the D10, D50 and D90 of the α-type silicon carbide powder and the β-type silicon carbide powder were as shown in Table 1. The obtained honeycomb structure had a diameter of 75 mm, a length in the cell extension direction of 33 mm and a cell density of 57 cells / cm. 2 The partition walls had a thickness of 0.3 mm. The formed electrode parts each had a thickness of 230 μm, and the central angle (the angle defined by the central axis and the line connecting both ends of each electrode part) in the cross section in the direction perpendicular to the flow path direction of the honeycomb structure part was 45°. The volume resistivity of the electrode parts was 0.40 Ω cm, and the porosity was 32.5%. Furthermore, the D10, D50 and D90 of the silicon carbide in the electrode parts were as shown in Table 1.

[0065] (Formation of thermal spray base layer) Metal (SUS430) powder, glass (MgO-Al 2 O 3 -SiO 2 ) powder, methylcellulose, glycerin, and water were mixed with a rotating and revolving mixer to prepare a base layer forming paste. Here, the metal powder and the glass powder were mixed so that the volume ratio of the metal powder:glass powder was 40:60. In addition, when the total of the metal powder and the glass powder was 100 parts by mass, the amount of methylcellulose was 0.5 parts by mass, the amount of glycerin was 10 parts by mass, and the amount of water was 38 parts by mass. The average particle diameter of the metal powder was 10 μm. The average particle diameter of the glass powder was 5 μm. Next, the base layer forming paste was applied so as to partially cover the electrode part formed above, and a honeycomb structure with the base layer forming paste was obtained. Next, the honeycomb structure with the base layer forming paste was dried with hot air at 80 ° C for 1 hour, and then fired under conditions of 1000 ° C for 2 hours in an argon atmosphere to form a thermal spray base layer. In this way, the honeycomb structure of this example was obtained. The obtained honeycomb structure was subjected to the evaluation of (4) above. The results are shown in Table 1.

[0066] <Examples 2 to 16 and Comparative Examples 1 to 7> A honeycomb structure was obtained in the same manner as in Example 1, except that the blending ratio of the metallic silicon powder, α-type silicon carbide powder, and β-type silicon carbide powder in the electrode portion-forming paste, and their D10, D50, and D90 were changed as shown in Table 1. The volume resistivity and porosity of the electrode portion, and the D10, D50, and D90 of the silicon carbide in the electrode portion were as shown in Table 1. The obtained honeycomb structure was subjected to the same evaluation as in Example 1. The results are shown in Table 1.

[0067] [Table 1]

[0068] As is clear from Table 1, in the honeycomb structures according to the examples of the present invention, the resistance of the electrode portions is adjusted to a low resistance region, and the continuity with the thermal sprayed base layer is also excellent. [Industrial Applicability]

[0069] The honeycomb structure according to the embodiment of the present invention and the electrically heated carrier using the same can be suitably used for treating (purifying) exhaust gas from automobiles. [Explanation of symbols]

[0070] 10a 1st end surface 10b 2nd end face 20 cells 30 Bulkhead 40 Peripheral wall 100 Honeycomb structure 120 Electrode section 200 Honeycomb structure

Claims

1. a honeycomb structure having an outer peripheral wall and partition walls disposed inside the outer peripheral wall and extending from a first end face to a second end face to define a plurality of cells forming flow paths; a pair of electrode portions disposed on an outer peripheral surface of the outer peripheral wall of the honeycomb structure portion, the electrode portion is composed of a porous body in which silicon carbide particles are bound by a binder, The volume resistivity of the electrode portion is 0.07 Ω cm to 1.2 Ω cm, the silicon carbide includes α-type silicon carbide and β-type silicon carbide, the silicon carbide has a volume-based cumulative particle size distribution D50 of 10 μm to 25 μm; The α-type silicon carbide has a D50 of 10 μm to 45 μm, and the β-type silicon carbide has a D50 of 10 μm to 45 μm. Honeycomb structure.

2. 2. The honeycomb structure according to claim 1, wherein the content of said α-type silicon carbide in said silicon carbide is 5% by mass to 95% by mass.

3. 3. The honeycomb structure according to claim 1, wherein the binder comprises metal silicon and / or metal silicide.

4. A honeycomb structure according to any one of claims 1 to 3; a pair of metal terminals provided on the pair of electrode portions of the honeycomb structure; An electrically heated carrier comprising:

5. The electrically heated support according to claim 4 , further comprising a base layer provided between the electrode portion of the honeycomb structure and the metal terminal.

6. An electrically heated carrier according to claim 4 or 5; A can body for holding the electrically heated carrier; An exhaust gas treatment device comprising:

Citation Information

Patent Citations

  • Method of mud shielding construction

    JP1983083795A

  • Copying device

    JP1984065862A

  • Magnetoresistance effect type magnetic sensitive element

    JP1988064374A

  • Honeycomb structure body

    JP2013198887A

  • Honeycomb structure and method for producing the same

    JP2014198318A